INTRASPECIFIC POLYPLOIDY IN CONIOGRAMME FRAXINEA (PTERIDACEAE) OF JAVA - Titien Ngatinem Praptosuwiryo (Floribunda, 2011)
Cytological study on Coniogramme fraxinea (D. Don) Diels has been carried out by observing 15 collection numbers of Javanese specimens collected from 6 localities. Somatic chromosome observation revealed that C. fraxinea of Java comprises of two cytotypes based on the basic chromosome number x = 30, viz.: 2n = 60 (diploid) and 2n = 120 (tetraploid). It is first cytological record of C. fraxinea in Java. Two variants reported here are recognized mainly by the coloration of frond, viz. frond with white striped lamina (WSL) and those with full green lamina (FGL). The diploid type is more common, widely distributed and consists of two variations (WSL and FGL). The tetraploid (three individuals) are WSL.